2020
DOI: 10.15587/2519-8025.2020.217554
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the anticancer properties of cis- and trans-diadamanthylcarboxylates of dirhenium(III)

Abstract: The aim of the study. The aim of the work was to investigate in vivo anticancer activity of cis- and trans-diadamanthylcarboxylates of dirhenium(III) alone and together with cisplatin in form of nanobins.Materials and methods. Model of tumor growth, Guerin’s carcinoma; intraperitoneal administration of cisplatin, dirhenium(III) compounds in liposomes and of binary liposomes, containing both cytostatics; volumes and final weights of tumors were measured.Results. In vivo antitumor properties of two dirhenium(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…12 Icsel et al, also reported novel platinum bases complexes whose cis-congeners showed more activity than those of the trans. 13 The in vivo anticancer properties of rhenium complexes reported by Shtemenko et al, 14 also revealed that the cis-analogue is slightly more active than the trans-analogue. Several factors are reported to be responsible for this activity; the cis-isomers are found to be less stable and lower in energy compared to the trans-isomers; 15 hence, making it easy for the leaving group to be cleaved and subsequently bind to the DNA.…”
Section: Introductionmentioning
confidence: 95%
“…12 Icsel et al, also reported novel platinum bases complexes whose cis-congeners showed more activity than those of the trans. 13 The in vivo anticancer properties of rhenium complexes reported by Shtemenko et al, 14 also revealed that the cis-analogue is slightly more active than the trans-analogue. Several factors are reported to be responsible for this activity; the cis-isomers are found to be less stable and lower in energy compared to the trans-isomers; 15 hence, making it easy for the leaving group to be cleaved and subsequently bind to the DNA.…”
Section: Introductionmentioning
confidence: 95%